Meningkatkan Semangat Kemerdekaan Peserta Didik Di SDN 056604 Purwobinangun Desa Emplasmen Kecamatan Sei Bingai Kabupaten Langkat - Assyifa Alfianda; Astuti Handayani; Cahyan Syari; Sa’I Frida Rejeki; Aprilla Putri; Rusi Ulfa Hasanah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of outreach to this school through community service activities is to increase the spirit of independence of students at SDN 056604 Purwobinangun, Emplasmen Village, Sei Bingai District, Langkat Regency. By participating in all the activities at the school, our socialization team plays a role in giving extraordinary enthusiasm to the students. The results of the outreach carried out by the socialization team to students showed that students had high enthusiasm for learning and enthusiasm in welcoming the Republic of Indonesia's independence day. The outreach team invites students to continue to remember the services of our independence heroes who died on the battlefield to defend and defend Indonesia so that Indonesia could become independent. With the program that has been held by the socialization team, we hope that we can strengthen relationships and increase insight and enthusiasm for students to become future generations of the nation who have a strong heroic spirit, are obedient, responsible and intelligent in the future.